2012
DOI: 10.1097/nrl.0b013e31826a99a1
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya Disease Can Masquerade as Multiple Sclerosis

Abstract: MM can be misdiagnosed as MS, leading to delay in correct treatment. We highlight the clinical and radiologic features which allow differentiation of these conditions early in the course, when treatment can have maximum benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Multiple sclerosis (MS) is an inflammatory disease of the white matter of the brain characterized by relapsing neurological symptoms. The masquerade between those diseases is high, but the clinical, radiological and laboratory investigations confirm that both pathologies were present in our patient, although this is not reported before 4 . The studies emphasize early consideration of Moyamoya in the differential diagnosis of MS-spectrum disorders, which shares many features 4,5 .…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Multiple sclerosis (MS) is an inflammatory disease of the white matter of the brain characterized by relapsing neurological symptoms. The masquerade between those diseases is high, but the clinical, radiological and laboratory investigations confirm that both pathologies were present in our patient, although this is not reported before 4 . The studies emphasize early consideration of Moyamoya in the differential diagnosis of MS-spectrum disorders, which shares many features 4,5 .…”
supporting
confidence: 60%
“…It was found that most cases initially are considered being compatible with multiple sclerosis; stroke and the typical angiography finding change the diagnosis to Moyamoya and this is a unique about our case report 4,5,11 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Some clinicians have effectively combined in the treatment of MMD and emphasized the roles of temporalis, dura mater, and superficial temporal artery (STA) in blood supply. The symptoms of cerebral ischemia and epilepsy are alleviated significantly in most patients after successful implementation of revascularization (Bao et al, 2012;Dorfman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Here is the basis for differential diagnosis. Firstly, MM commonly has paroxysmal onset and recovers within 24 h, whereas MS attacks may progress in a subacute manner after several days (7). Secondly, the clinical presentations of MM include transient ischemic attacks, ischemic stroke, hemorrhagic stroke, seizures, headache, and cognitive impairment (23).…”
Section: Ob (+) Vep (+) Dissemination Of Lesions In Space (Dis) Anmentioning
confidence: 99%